Consequences of Folding the Mitochondrial Inner Membrane - Mannella, Carmen A. (Frontiers in Physiology, 2020)
A fundamental first step in the evolution of eukaryotes was infolding of the chemiosmotic membrane of the endosymbiont. This allowed the proto-eukaryote to amplify ATP generation while constraining the volume dedicated to energy production. In mitochondria, folding of the inner membrane has evolved into a highly regulated process that creates specialized compartments (cristae) tuned to optimize function. Internalizing the inner membrane also presents complications in terms of generating the folds and maintaining mitochondrial integrity in response to stresses. This review describes mechanisms that have evolved to regulate inner membrane topology and either preserve or (when appropriate) rupture the outer membrane.